Pendekatan Komunikatif dalam Pembelajaran Bahasa Arab dan Implementasinya untuk Meningkatakan Maharatul Kalam - Udin Zainudin (Program Studi Pendidikan Agama Islam, 2024)
Most beginner Arabic language learners experience difficulties when learning it. The stigma of this difficulty arises because Arabic language teachers focus too much on learning rules such as; nahwu, shorof and balaghah, this makes learning boring and difficult, even though the rules of nahwu and shorof are only a small part of the Arabic language. The main purpose of learning Arabic is communication, sharing experiences and stories. The aim of this research is to provide an option for an approach in learning Arabic to improve maharatul kalam. This type of research is conceptual research, secondary data is collected from secondary sources such as books and journals related to the research object. The research results show that the communicative approach is very effective, easier and more enjoyable for Arabic language learners, implementing learning using direct methods, with the tadrib bi'ah lughowiyah technique in improving maharatul kalam skills without memorizing vocabulary.